EVALUASI PELAKSANAAN CARA DISTRIBUSI OBAT YANG BAIK PADA APOTEK DI KECAMATAN MLATI KABUPATEN SLEMAN YOGYAKARTA - , ISNA SUGIH HARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Drugs distribution is an important process in maintaining the efficacy, safety, and quality of drug after manufacturing process. Good Drug Distribution Practice have to implemented at distribution facilities include pharmacy to make sure that drug quality can be maintained until the drug is consumed by the patient. Therefore, this study aims to describe the implementation of Good Drug Distribution Practice and follow up that may be applied to pharmacies on Mlati District, Sleman Regency, Yogyakarta. This study was a non experimental-qualitative and descriptive analysis, there were nine pharmacies (A, B, C, D, E, F, G, H, and I) as a sample. The data was collected by using checklist which filled in by researcher, based on direct interview with pharmacist at pharmacy on that time. The checklist includes profile aspect of facilities, buildings and equipment, procurement, receipt and storage, distribution, handling of recall product and expiration, extermination, and others. The data obtained and analyzed qualitatively to determine the follow-up that may be applied to the pharmacies that have not been qualified based on level of criticality of the findings. The result showed 100% pharmacy at Mlati District (A, B, C, D, E, F, G, H, and I) are not qualified on CDOB. Follow up that may be applied to the pharmacy on Mlati District, Sleman Regency, Yogyakarta is 88,89% ( pharmacies A, B, C, D, E, G, H, and I) a stern warning, and 11,11% (pharmacies F) suspension of activities.